Hybridity in Morrison`s "The bluest eye": the dialogic formation of Claudia`s self - Del Guercio, Gerardo (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Toni Morrison`s stories have centered on reciting life stories, mounting new and individual ideas of the self. The present essay revisits Morrisom`s first book, "The Bluest Eye", to consider her first female her, Claudia, and her hybrid growth. Hybridity is used, in "The Bluest Eye", as a narrative approach to craft Claudia`s self through the course of the novel, enabling her gallant endurance within an antagonistic cultural milieu.
Keywords: Morrison, Toni (1931-2019); "The Bluest Eye"; hybridity; Bhabha, Homi (1949- ); Bachtin, Michaił Michajłowicz (1895-1975)